Improving Valproate Prescribing Practices in Women of Childbearing Age: An Audit Cycle in a Psychiatric Inpatient Setting in Qatar - Ahmad Alater; Zidan Masoudi; Sazgar Hamad; Majid Al Abdulla; Yousaf Iqbal (BJPsych Open, 2025)
Aims: Prescribing valproate to women of childbearing age in psychiatric settings requires a nuanced approach due to its teratogenicity. The Medicines and Healthcare Products Regulatory Agency (MHRA) and the National Institute for Health and Care Excellence (NICE) guidelines emphasize the importance of avoiding valproate in this population, considering alternative medications, discussing benefits, side effects, and teratogenicity, conducting pregnancy testing before initiation, and ensuring the use of highly effective contraception. This study aimed to evaluate current prescribing practices against MHRA and NICE guidelines within Hamad Medical Corporation (HMC) psychiatric inpatient units.